Dynamics of Immigration Policy in Facing Global Mobility - Daffa Raihan Arya Mas'adi (Indonesian Economic Review, 2024)
Increasing global mobility due to globalization requires every country to have an adaptive and responsive immigration policy. Immigration policy plays a role in balancing national interests, security and openness to global dynamics. This study aims to analyze the dynamics of immigration policies in various countries in dealing with international migration flows and identify the challenges and implications of these policies on social, economic and political aspects. This research uses a qualitative approach with descriptive-analytical methods. Data was collected through a literature study which included analysis of immigration policy documents, international regulations, official government reports and related academic journals. Data analysis techniques are carried out by reducing data, presenting data, and drawing conclusions inductively to identify policy patterns implemented in various countries. In addition, this research applies source triangulation techniques to increase data validity by comparing various references from academic studies, government policies, and reports from international organizations such as IOM and UNHCR. The research results show that immigration policy continues to develop following global geopolitical, economic and social changes. Countries face a dilemma in balancing security aspects with openness to migrant workers and refugees. Some countries apply a selective, skills-based approach, while others focus more on protection and humanitarian aspects. This study emphasizes the importance of immigration policies that are flexible, evidence-based, and prioritize a balance between strict regulations and ease of mobility to support national stability and international cooperation.